Mild to Severe Anemia of Undiagnosed Etiology Diagnosed by Genetic Study - Bose, Kalliol; Siddique, Md Abu Bakkar; Ghorai, Sudipta; Kundu, Chanchal; Saha, Sudip (Journal of Nepal Paediatric Society, 2016)
We report a case of a child with beta thalassemia major, whose mother is a carrier of beta thalassemia and father is having hereditary persistence of fetal hemoglobin. Gene study revealed compound heterozygous for codon 8/9+G and IVS-1-5 G>C point mutation. Another four cases of anemia not responding to iron diagnosed to have alpha thalassemia carrier are also reported here. J Nepal Paediatr Soc 2016;36(2):213-215.